Performance rating and yardstick competition in social service provision - Federico Revelli (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper investigates whether national evaluation of decentralised government performance tends, by lessening local information spill-overs, to reduce the scope for local performance comparisons and consequently to lower the extent of spatial auto-correlation among local government expenditures. It analyses UK local government expenditures on personal social services before and after the introduction of a national performance assessment system (SSPR, Social Services Performance Rating) that would attribute a rating to each local authority. The empirical evidence suggests that the introduction of the SSPR has substantially reduced policy mimicking among neighboring jurisdictions.
Keywords: H72; C21; H77; 330; social services; welfare competition; information spill-overs; spatial autocorrelation; Kommunale Dienstleistung; Sozialer Dienst; Yardstick Competition; Benchmarking; Spillover-Effekt; Kommunale Ausgaben; Räumliche Interaktion; Schätzung; Großbritannien